Application of DEA method in efficiency evaluation of public higher education institutions - Nazarko, Joanicjusz; Šaparauskas, Jonas (Technological and Economic Development of Economy, 2014)
Public higher education sector is under a growing pressure worldwide to increase efficiency and improve the quality of its activities. Limited financial resources as well as detailed regulations and supervision of their spending are the important features of the public higher education sector. Another important and debated issue is the division of public money among higher education institutions (HEI). It is therefore crucial to create stimuli for the rational management of public funds by HEI and for the quality improvement of HEI services. One of the proposed ways to achieve the desired result is the comparative efficiency assessment of HEI activities. Setting clear reference points for HEI, such assessment may be treated as a substitute for market competition.This paper describes a comparative efficiency study of 19 Polish universities of technology. Detailed analysis of potential input, output and environmental variables describing the HEI efficiency model was carried out. The study used the CCR-CRS output-oriented DEA model. It was assumed that HEI had more influence on achieved results than on the amount of their resources. The economies of scale were also studied in relation to the efficiency achieved. Sensitivity of the model to data errors was tested.First published online: 28 Jan 2014